Populus NST/SND orthologs are key regulators of secondary cell wall formation in wood fibers, phloem fibers and xylem ray parenchyma cells. (26th February 2019) - Takata, Naoki; Awano, Tatsuya; Nakata, Miyuki T; Sano, Yuzou; Sakamoto, Shingo; Mitsuda, Nobutaka; Taniguchi, Toru
Abstract: Wood fibers form thick secondary cell wall (SCW) in xylem tissues to give mechanical support to trees. NAC SECONDARY WALL THICKENING PROMOTING FACTOR3/SECONDARY WALL-ASSOCIATED NAC DOMAIN PROTEIN 1 ( NST3/SND1 ) and NST1 were identified as master regulators of SCW formation in xylem fiber cells in the model plant Arabidopsis thaliana . In Populus species, four NST/SND orthologs have been conserved and coordinately control SCW formation in wood fibers and phloem fibers. However, it remains to be elucidated whether SCW formation in other xylem cells, such as ray parenchyma cells and vessel elements, is regulated by NST/SND orthologs in poplar. We knocked out all NST/SND genes in hybrid aspen using the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 nuclease (Cas9) system and investigated the detailed histological appearance of stem tissues in the knockout mutants. Observation by light microscopy and transmission electron microscopy showed that SCW was severely suppressed in wood fibers, phloem fibers and xylem ray parenchyma cells in the knockout mutants. Although almost all wood fibers lacked SCW, some fiber cells formed thick cell walls. The irregularly cell wall-forming fibers retained primary wall and SCW, and were mainly located in the vicinity of vessel elements. Field emission-scanning electron microscope observation showed that there were no apparent differences in the structural features of pits such as the shape and size between irregularly SCW-forming wood fibers in the knockout mutants and normal wood fibers in wild-type. Cell wall components such as cellulose, hemicellulose and lignin were deposited in the cell wall of irregularly SCW-forming wood fibers in quadruple mutants. Our results indicate that four NST/SND orthologs are master switches for SCW formation in wood fibers, xylem ray parenchyma cells and phloem fibers in poplar, while SCW is still formed in limited wood fibers, which are located at the region adjacent to vessel elements in the knockout mutants.